Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am learning Measure theory via self study of Bartle "The elements of Integration and Lebesgue Measure". I was stumped by the reasoning in one of the decomposition proofs. The point is to show that a Bounded Linear Functional can be represented as the difference of two positive bounded linear functionals. The proof presented is as follows.

Define $G^+ = sup\{G(f) : g \in L_p : 0 \le g \le f\}$ for all $f \ge 0$.

The next step is to ST $G^+$ is a BLF (Bounded Linear Functional).

It is clear that $G^+(cf) = c G^+ (f)$ for $c \ge 0$, $f \ge 0$ (This part was not a problem). The next step attempts to prove that given

$f_j \ge 0, G^(f_1 + f_2) = G^+(f_1) + G^+(f_2)$

This is where I got confused and did not quite understand the line of reasoning. This is how the proof continues:

If $0 \le g_j \le f_j$ Then $G(g_1) + G(g_2) = G(g_1 + g_2) \le G^+(f_1 + f_2)$

Taking supremum over all $g_j \in L_p$ we claim that

$G^+(f_1) + G^+(f_2) \le G^+(f_1 + f_2)$

I would have thought that it would be te other way around, i.e.

$sup\{G(g_1) : g_1 \in L_p, 0 \le g_1 \le f_1 \}$ + $sup\{G(g_2) : g_2 \in L_p, 0 \le g_2 \le f_2 \}$ >= $sup\{G(g_1 + g_2) : g_1, g_2 \in L_p, 0 \le g_j \le f_j\}$

Which implies $G^+(f_1) + G^+(f_2) \ge G^+(f_1 + f_2)$

The book continues: Conversely if $0 \le h \le f_1 + f_2$ let $g_1 = sup(h - f_2,0)$ and $g_2 = inf(h, f_2)$.

It follows that $g_1 + g_2 = h$ and that $0 \le g_j \le f_j$. Threfore

$G(h) = G(g_1) + G(g_2) \le G^+(f_1) + G^+(f_2)$

Since this is true for all $h \in L_p$ we have $G^+(f_1 + f_2) = G^+(f_1) + G^+(f_2)$

My questions were:

  1. Why would $G^+$ be positive?

  2. How did the final conclusion $G^+(f_1 + f_2) = G^+(f_1) + G^+(f_2)$ for f_1, f_2 in L_p follow?

I would have thougt that the definition for $G^+$ should have been

$G^+ = sup\{G(f) : g \in L_p : 0 \le g \le f, G(g) \ge 0\}$

share|cite|improve this question

I think that the definition of G^+ should be this: $G^+(f)=\sup\{G(g): g \in L_p,\, 0\leq g\leq f\}$, for $f\geq 0$.

Ad 1. I think it is obvious, If $f\geq 0$, then $\mathbb{0} \in \{g\in L_p: 0\leq g \leq f\}$ and $G(0)=0$, so the supremum can't be less than $0$.

Ad 2. Let $$A(f)=\{g\in L_p: 0\leq g \leq f\},$$ for $f\geq 0$. It is obvious (by definition of $G^+$) that $$G(g_1)+G(g_2)=G(g_1+g_2)\leq G^+(f_1+f_2),$$ for $g_j \in A(f_j)$, $j=1,2$ (becouse $g_1+g_2\in A(f_1+f_2)$). So now,at the first we take supremum over all $g_1$ and we obtain: $$\sup\limits_{g_1\in A(f_1)} G(g_1)+G(g_2)\leq G^+(f_1+f_2),$$ next we take supremum over all $g_2$ and we obtain: $$\sup\limits_{g_1\in A(f_1)}G(g_1)+\sup\limits_{g_2\in A(f_2)}G(g_2)=\sup\limits_{g_2\in A(f_2)}(\sup\limits_{g_1\in A(f_1)} G(g_1)+G(g_2))\leq G^+(f_1+f_2),$$

In the proof of the opposite inequality we just use the fact that taking $h \in A(f_1+f_2)$ we can define $g_1 \in A(f_1)$ and $g_2 \in A(f_2)$ (then $G(g_j)\leq G^+(f_j)$, for $j=1,2$) such that $h=g_1+g_2$ and use the linearity of $G$.

I hope that I helped :)

share|cite|improve this answer
Thanks for your response. I think I get it. – Ramesh Kadambi Jul 29 '11 at 22:33

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.